2018
DOI: 10.1371/journal.pone.0192915
|View full text |Cite
|
Sign up to set email alerts
|

Perceived behavioral control as a potential precursor of walking three times a week: Patient's perspectives

Abstract: BackgroundBehavior change theories can identify people’s main motivations to engage in recommended health practices and thus provide better tools to design interventions, particularly human centered design interventions.ObjectivesThis study had two objectives: (a) to identify salient beliefs about walking three times a week for 30 minutes nonstop among patients with hypertension in a low-resource setting and, (b) to measure the relationships among intentions, attitudes, perceived social pressure and perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Perceived behavioral control was a significant predictor of employee intention to get up and do "The Big 3" and had the highest regression weight. This finding supports previous researchers who also reported that out of the three global constructs in the RAA, perceived behavioral control has the highest regression weight for predicting PA behavior intention (Busse & Miranda, 2018;Conner et al, 2017). This study observed a low average number of days employees got up and did three separate light intensity neuromotor PA movements at work regardless of their enrollment status in a worksite wellness PA program.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Perceived behavioral control was a significant predictor of employee intention to get up and do "The Big 3" and had the highest regression weight. This finding supports previous researchers who also reported that out of the three global constructs in the RAA, perceived behavioral control has the highest regression weight for predicting PA behavior intention (Busse & Miranda, 2018;Conner et al, 2017). This study observed a low average number of days employees got up and did three separate light intensity neuromotor PA movements at work regardless of their enrollment status in a worksite wellness PA program.…”
Section: Discussionsupporting
confidence: 90%
“…The statistical significance of perceived norm in predicting employee intention to get up and do "The Big 3" at work complements the previous finding of sub-study 1. This "popular" variable was a significant predictor of employee intention, which supports previous studies that show this construct as significant in predicting intention (Busse & Miranda, 2018;Hagger et al, 2002;Kerner & Grossman, 1998). Since intention is the most proximal factor that leads to behavior, university wellness programs can practically apply this finding by increasing efforts to make getting up and doing light intensity neuromotor PA at work a more popular and normative behavior.…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, motivation can be increased by establishing a supportive environment (Hill-Briggs et al, 2021). Social support can be done by involving the community in forming attractive health promotions and activities, as well as involving policy makers in making rules and providing awards (Busse & Miranda, 2018;Kristjansson et al, 2020). The low perceived behavior control in this study is estimated to be related to the respondent's age.…”
Section: The Relationship Between Perceived Behavior Control and Diab...mentioning
confidence: 89%
“…El método más utilizado para recolectar la información en los estudios cualitativos fue la entrevista semiestructurada [20][21][22][23][24] , otras herramientas empleadas fueron la entrevista estructurada [25][26][27] , grupos focales 22,23,28 y entrevistas en profundidad 19 ; para la elaboración del componente cuantitativo se realizaron encuestas y revisión de historia clínica 27,29,31 . Figura 1.…”
Section: Características De Los Estudios Incluidos Y Sus Participantesunclassified
“…Respecto a las barreras y facilitadores para realizar actividad física, Busse et al 26 identificaron las creencias de pacientes hipertensos peruanos de bajos recursos sobre caminar tres veces a la semana durante treinta minutos sin parar, encontrando la creencia de que puede ser dañino para la salud (sensación de fatiga, dolor de miembros inferiores), pereza, falta de tiempo, no compañía y tener que lidiar con malas condiciones temporales, urbanas y/o de tráfico. Oliveira et al 19 encontraron que tanto para pacientes adherentes como no adherentes a los medicamentos, la realización de ejercicios resulta desagradable; o que los espacios como parques o canchas son ocupados en muchas ocasiones para el desarrollo de prácticas ilícitas como lo menciona Mejía et al 24 .…”
Section: "No Me Gusta Tomar Medicamentos Solo Cuando Me Lo Indica El ...unclassified